Aplikasi Edible Coating dari Lidah Buaya dan Karagenan untuk Memperpanjang Umur Simpan Buah Tomat (Lycopersicum esculentum Mill.) - Siregar, Tagor M.; Elysia, Vanessa (Faculty of Agricultural Technology, University of Jember, 2024)
Tomato fruit (Lycopersicum esculentum Mill.) is a food material with a high water content so it is easy to decompose. This shows that efforts to prevent reduction in food quality can be developed in the form of edible coating from aloe vera gel with concentration of 0%, 30%, 40%, and 50%, and carrageenan with concentration of 1%, 2%, and 3%. The aims of this research were to determine the concentration of aloe vera gel and carrageenan based on the characteristics of edible film and to determine the effect of edible coating and storage time on the quality of tomato. The first stage of this research is making edible film based on analysis parameters such as water vapor transmission rate (WVTR), tensile strength, elongation, and thickness. The selected concentration used in the second stage of this research for making edible coating was 40% of aloe vera gel and 3% of carrageenan. The selected concentration has a WVTR value of 1.758±0.20 g.mm/m2.hour, tensile strength value of 0.248±0.00 N/cm2, elongation value of 25.164±0.10%, and thickness value of 0.074±0.00 mm. Tomato samples coated with edible coating and control tomatoes is stored for 9 days at room temperature (24-25oC and 65–70% relative humidity aproximately) and samples are analyzed every 3 days based on analysis parameters such as vitamin C content, weight loss, hardness level, pH, ohue, lycopene content, and total dissolved solids value. The application of edible coating and storage time can inhibit the decrease of vitamin C levels, lycopene levels, weight loss, hardness, also can inhibit the increase in pH value and total dissolved solids value. Meanwhile, the change in color (hue) of tomato is not affect by the use of edible coating. Keywords: aloe vera, carrageenan, edible coating, storage time, tomato